Pengaruh Pengetahuan Wajib Pajak, Tarif Pajak, Penyuluhan Pajak, Penggunaan Media Elektronik, dan Lingkungan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Badan di Kantor Pelayanan Pajak Pratama Pamekasan - Desinta Fitria Dewi; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2023)
The purpose of this thesis is to find out about the Effect of Taxpayer Knowledge, Tax Rates, Tax Counseling, Use of Electronic Media, and Taxpayer Environment on Corporate Taxpayer Compliance at the Tax Service Office (KPP) Pratama Pamekasan. This research is a quantitative research using associative research type. The data collection technique was obtained by conducting interviews. The results of this study found that Taxpayer Knowledge, Tax Rates, Tax Counseling, and Use of Electronic Media had an effect on Taxpayer Compliance while the Taxpayer's Environment had no effect. Suggestions for further researchers to add other variables and expand the research location not only in one place.Keywords: Taxes, Taxpayer Knowledge, Tax Rates, Tax Counseling, Use of Electronic Media, Taxpayer Environment, and Taxpayer Compliance.